Asset-ing the extreme poor: experiences and lessons from a BRAC project - Marin, Imran; Begum, Shamim Ara (BRAC, 2019)
The Jamalpur Flood Rehabilitation Project (JFRP) was designed to provide flood rehabilitation to women who were not targeted in the previous ECHO/NOVIB/BRAC flood rehabilitation project of 1998/1999, in which, mainly BRAC group members received flood rehabilitation inputs. In response to the 1998 flood, many donors funded NGOs which delivered rehabilitation inputs to their own members. This was a concern as the extreme poor, who suffer the most damaging losses in any natural disaster, tend to be under represented in the NGO membership profile. This project was designed to assist very poor women who were not associated with NGOs and thus were left out of the 1998 flood rehabilitation programs. The objective of the project was to provide rehabilitation assistance to poor women through a range of assets with a view to push them towards self-sustenance and to link them with existing development programs. The project aimed to involve 3400 hard-core poor women in income-generating activities and employment enabling them to earn a living and recover damages incurred due to floods. This research was carried out during a time when the project was about a year old. Thus, impact assessment was not the idea behind this work. It was designed to address two broad themes: (1) targeting effectiveness and (2) asset specific issues, such as preliminary ideas of benefits received, challenges faced and future possibilities. For the first theme, the project used a set of targeting indicators on which information was collected through survey questionnaire. In addition to this, we asked some basic questions related to poverty dynamics around two assets-- homestead land and crop land. We developed separate sections for each asset focussing on benefits, challenges and future possibilities. We find that this project has been very effective in targeting the extreme poor. This success is commendable as it involved the development of good indicators, based on a synthesis of poverty literature and programmatic knowledge gleaned from considerable BRAC experiences dealing with poverty. One recurrent theme that emerges in this paper is that the real challenge in providing the critical push in the lives of the extreme poor involves bringing about critical changes in the agencies of the extreme poor. This has to be achieved at the individual level and also at deeper and intermediate levels affecting the reproduction of the poverty trap. Ensuring the economical/technical aspects of asset returns and its viability are not sufficient in themselves, changes will have to be made in the settings in which the extreme poor conduct their lives.